Antibacterial Activity Test Of Methanolic Extract Of Rambutan Leaves (Nephelium Lappaceum L.) Against Propionibacterium Acnes Growth - Cucu Arum Dwi Cahya; Desi Elmasari Manik (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Diseases caused by bacterial infections remain one of the leading health problems in Indonesia. Infections are among the most common illnesses suffered by the population, including skin infections such as acne (acne vulgaris). Therefore, alternative solutions are needed to address this issue by utilizing antimicrobial compounds derived from plants. One commonly used medicinal plant comes from the Sapindaceae family. A species from this family, the rambutan leaf (Nephelium lappaceum L.), has been reported to inhibit the growth of Propionibacterium acnes. Objective: To determine whether methanol extract of rambutan leaves (Nephelium lappaceum L.) contains tannins, flavonoids, saponins, and terpenoids; to assess its ability to inhibit the growth of Propionibacterium acnes; and to identify the most effective concentration among 15%, 35%, and 50% for antibacterial activity. Methods: The antibacterial activity was tested using the disc diffusion method to evaluate the potential of rambutan leaf extract as an antibacterial agent. Results: The study showed that the methanol extract of rambutan leaves inhibited the growth of Propionibacterium acnes, with inhibition zone diameters of 7.4 mm (15%), 9.53 mm (35%), and 11.53 mm (50%). The positive control showed an inhibition zone of 15.3 mm, while the negative control showed no antibacterial activity. Conclusion: The results indicate that the methanol extract of rambutan leaves exhibits antibacterial activity that increases with concentration, with the highest effectiveness observed at 50%. This activity is presumed to be due to the presence of secondary metabolite compounds that inhibit the growth of Propionibacterium acnes.